Molecular consequences of truncations of the first exon for in vitro splicing of yeast actin pre-mRNA. - Duchêne, M (Nucleic Acids Res, 1988)
A defined minimum length of the first exon is required for the generation of spliced products from a synthetic yeast actin mRNA-precursor in vitro. If the first exon is 1, 2, 3 or 5 nucleotides long, only the first step of the splicing reaction can take place. A transcript starting with the first nucleotide of the intron does not get converted into any of the normally obtained splicing products or intermediates. On the other hand, spliceosome assembly does not depend on the presence of a first exon. IMAGES: